The Effect of Online Shopping and E- Wallet on Society 5.0 Lifestyle in the Perspective of Islamic Economics - Aulya Nurrachma; Yenni Rohmatun; Usman; Eni Nuraeni (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
This research is to obtain the significance value of online shopping and e-wallet variables on lifestyles in the era of society 5.0 and views of the Islamic economy. The study used a mixed sequential explanatory design method, using quantitative to measure variables with multiple linear regression and a qualitative library for the perspective of Islamic economics. The data used is primary from the distribution of questionnaires who are domiciled in Cirebon, Majalengka, Kuningan and secondary data from the Al-Qur'an, Hadith, and fiqh rules. The data was tested using SPSS version 29. This study shows that online shopping (X₁) and e-wallets (X₂) have a significant and positive effect on lifestyle (Y) partially. The significance value at X₁ is 0.003 <0.05 with a tcount of 3.068 > ttable of 1.655 and at X₂ of 0.000 <0.05 with a tcount of 5.215 > ttable of 1.655. The two variables simultaneously influence the Y variable, with a significance value of 0.000 <0.05 and Fcount 52.468 > Ftable 2.34. Online shopping and e-wallets for lifestyle in the era of society 5.0 based on an Islamic economic perspective may be carried out by paying attention to the sharia according to the DSN MUI fatwa. Penelitian ini untuk memperoleh nilai signifikansi dari variabel belanja online dan e-wallet terhadap gaya hidup di era society 5.0 serta pandangan ekonomi Islam. Penelitian menggunakan mix methods desain sequential explanatory, dengan menggunakan kuantitatif untuk mengukur variabel dengan regresi linear berganda dan kualitatif library untuk perspektif ekonomi Islam. Data yang digunakan primer dari persebaran kuesioner yang berdomisili di Cirebon, Majalengka, Kuningan dan data sekunder dari Al-Qur’an, Hadits, serta kaidah fiqih. Data diuji menggunakan SPSS versi 29. Penelitian ini menunjukkan bahwa belanja online (X₁) dan e-wallet (X₂) berpengaruh secara signifikan dan positif terhadap gaya hidup (Y) secara parsial. Nilai signifikansi pada X₁ yakni 0,003 < 0,05 dengan thitung 3,068 > ttabel 1,655 dan pada X₂ sebesar 0,000 < 0,05 dengan thitung 5,215 > ttabel 1,655. Kedua variabel berpengaruh secara simultan terhadap variabel Y, dengan nilai signifikansi 0,000 < 0,05 dan Fhitung 52,468 > Ftabel 2,34.  Belanja online dan e-wallet terhadap gaya hidup di era society 5.0 berdasarkan perspektif ekonomi Islam boleh dilakukan dengan memperhatikan syariat yang sesuai fatwa DSN MUI.